My Baby's Movements: a stepped wedge cluster randomised controlled trial to raise maternal awareness of fetal movements during pregnancy study protocol - V. Flenady; G. Gardener; F. M. Boyle; E. Callander; M. Coory; C. East; D. Ellwood; A. Gordon; K. M. Groom; P. F. Middleton; J. E. Norman; K. A. Warrilow; et al. (BMC, 2019)
Abstract Background Stillbirth is a devastating pregnancy outcome that has a profound and lasting impact on women and families. Globally, there are over 2.6 million stillbirths annually and progress in reducing these deaths has been slow. Maternal perception of decreased fetal movements (DFM) is strongly associated with stillbirth. However, maternal awareness of DFM and clinical management of women reporting DFM is often suboptimal. The My Baby's Movements trial aims to evaluate an intervention package for maternity services including a mobile phone application for women and clinician education (MBM intervention) in reducing late gestation stillbirth rates. Methods/design This is a stepped wedge cluster randomised controlled trial with sequential introduction of the MBM intervention to 8 groups of 3-5 hospitals at four-monthly intervals over 3 years. The target population is women with a singleton pregnancy, without lethal fetal abnormality, attending for antenatal care and clinicians providing maternity care at 26 maternity services in Australia and New Zealand. The primary outcome is stillbirth from 28 weeks' gestation. Secondary outcomes address: a) neonatal morbidity and mortality; b) maternal psychosocial outcomes and health-seeking behaviour; c) health services utilisation; d) women's and clinicians' knowledge of fetal movements; and e) cost. 256,700 births (average of 3170 per hospital) will detect a 30% reduction in stillbirth rates from 3/1000 births to 2/1000 births, assuming a significance level of 5%. Analysis will utilise generalised linear mixed models. Discussion Maternal perception of DFM is a marker of an at-risk pregnancy and commonly precedes a stillbirth. MBM offers a simple, inexpensive resource to reduce the number of stillborn babies, and families suffering the distressing consequences of such a loss. This large pragmatic trial will provide evidence on benefits and potential harms of raising awareness of DFM using a mobile phone app. Trial registration ACTRN12614000291684. Registered 19 March 2014. Version Protocol Version 6.1, February 2018.